Distribution. N in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. N Atlantic Ocean at high latitudes, from NE Canada (Davis Strait S to Gulf of Saint Lawrence) to Greenland, Iceland, Jan Mayen, and Svalbard; seasonally, distribution extended N into the Arctic Ocean and S into the North Sea in the NE Atlantic Ocean. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 175, DOI: 10.5281/zenodo.6607185